Representations of correlations of the і [A, B] = f(A) + g(B) type - Samoilenko , Yu. S.; Shulman , V. S. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
It is proved that all nontrivial representations of quadratic relation i [A, B] = f(A) + g(B) with self-adjoint operators A, B are unbounded if f and g are nonnegative; for any f and g this relation does not have nontrivial finite-dimensional representations and factor-representations of type II_I, but can have infinite-dimensional irreducible representations with bounded operators.